ANALISIS FENOMENA SOSIAL PEKERJA ANAK DI DESTINASI WISATA PANTAI KUTA BALI - Fevi Chandra; Komang Shanty Muni Parwati; Firlie Lanovia Amir (MSJ : Majority Science Journal, 2023)
The existence of Pantai Kuta Bali as a favorite tourist destination on the Pulau Dewata is able to open the job vacancies for local people. Also for the children. Children under 18 years old here also work for 16 hours a day. Then this is becomes a social phenomenon which until now has not been resolved. This study aims to: 1) Knowing the background of the child labor in Pantai Kuta Bali; and 2) Knowing the perception of non-Balinese tourists and Balinese local people towards this social phenomenon. The research method used is qualitative. Data collection was carried out through the process of observation, interviews and documentation. Research informants consisted of 3 key informants with the technique of selecting informants using purposive sampling technique. Data analysis techniques include data reduction, data analysis and making conclusion. The result of this thesis show that the children in Pantai Kuta Bali work based on economic factor, encouragement from parents, environmental influences and the belief in myths in Desa Muntigunung. Meanwhile, the perception of tourists and the local people for this phenomenon show a perception that does not support the activities of working children.